(untitled) (Bangladesh Journal of Infectious Diseases, 2021)
The Coronavirus disease 2019 (COVID-19) outbreak, forcing us to face unprecedented moments in the world. The huge devastating impact of the world due to the covid-19 attack causes the brink of no return. However, there is no proven and specific treatment for Covid -19. Very few medications have received Emergency Use of Authorization. A recent in vitro study was the first time to find out and to assess the antiviral effect of Ivermectin on COVID-19. The study showed that Ivermectin was active against COVID- 19-infected cells, was able to kill effectively almost all viral particles within 48 h. In these moments of crisis, FDA-approved ivermectin is a ray of hope. Bangladesh Journal of Infectious Diseases 2020;7(2):95-98